Development of Ethno-STEM Learning Module based on Javanese Gamelan - Y. Yuliana; I. Nurwahidah; Y. Widiyawati (Universitas Negeri Yogyakarta, 2023)
Ethno-STEM can help students to learn the right learning concepts. The purpose of the study was to design, develop, and test the feasibility of the Ethno-STEM-based science learning module for class VIII students that was feasible to use. The module was printed teaching materials. The module aimed to make students learn independently and study anywhere and anytime without the need for supporting tools. The research development module refers to the Thiagarajan 4-D (Four-D) device development model with the stages of define, design, develop, and disseminate. The samples were 12 students of class VIII in SMP Institut Indonesia in the academic year 2021- 2022. The research instruments used validation sheets of learning material experts, learning media experts, practitioners, and student questionnaires. The feasibility of the module is reviewed based on the results of analyzed data. First, the validation of the Ethno-STEM-based learning module from the science learning validator, consisting of two learning material expert lecturers, obtained an overall score of 3.0 with good criteria. Second, the expert validation of learning media, consisting of 2 media expert lecturers, obtained an overall score of 3.60 with very good criteria. Third, the practitioner validation, consisting of two junior high school science teachers, obtained an overall score of 3.88 with very good criteria. And, student responses showed a percentage score of 94.8% with a very good category. Thus, the learning module of Ethno-STEM was feasible for science learning in class VIII of junior high school.